Importance of Suspecting a Hemorrhagic Intracranial Lesion as Metastatic Choriocarcinoma - Sharma, Upama; Shrestha, Dinuj; Dabadi, Sambardhan; Rajbhandari, Pravesh; Pant, Basant (Nepal Journal of Neuroscience, 2022)
Though the brain metastasis from gestational trophoblastic neoplasia is rare, incidence is 3-21.4%. In this article, we report the rare case of a young female, presented with the features of raised Intracranial Pressure (ICP) with intracranial space occupying lesion, who was treated for tubercular abscess because she was clinically diagnosed as case of pulmonary TB from core biopsy of lung mass and was under Anti tubercular treatment at other center and the differential diagnosis of cavernoma bleed made from imaging modalities. However, to our surprise the histopathology came out as metastatic choriocarcinoma. There was history of incomplete abortion 1 year back which could have developed from any gestational trophoblastic tissue resulting from a hydatidiform mole, miscarriage, or ectopic pregnancy. She gave this history after the histopathology came out as metastatic choriocarcinoma. The social tabu and going through traumatic experience, would be the region for her not to disclose the history before surgery. Although miscarriages are common and women continue to suffer in silence. The rarity of brain metastasis from gestational trophoblastic neoplasia, there are still no guidelines on treatment strategies for these patients yet.